Influencia de la terapia de reemplazo hormonal en la respuesta sexual de mujeres menopáusicas y posmenopáusicas atendidas en el hospital I Essalud Moyobamba. Octubre del 2003 - Marzo del 2004 - Torres Jara, Doris Charito (2004)
The purpose of this investigation was to evaluate the influence of HRT on Sexual Response menopausal and postmenopausal women I EsSalud Moyobamba Hospital between October 2003 - March 2004. For this purpose an analytical research was conducted Cases and Controls , cross-sectional, with prospective data collection. We worked with 120 women divided into two groups: an experimental group of 60 women (A) and a control group of 60 women equally (B). The experimental group "A" received HRT for varying periods of time, the same that were considered between 6 months to more than five years. • The group consisted of those women in menopause or menopause stage not receiving hormone replacement therapy for different reasons. Age in both groups ranged from 34 years to 60 years. Sexual Response: To collect the information a structured interview, in which the basic data to assess the influence of hormone replacement therapy on sexual response, the same that was calculated based were collected at three levels was used positive, indifferent and negative respectively. It was determined that Hormone Replacement Therapy (HRT) had a favorable influence on the sexual response of menopausal and postmenopausal women in the Hospital I EsSalud Moyobamba, so much so that 55 of the 60 women from the study group (who took HRT) responders positive unlike those women sex that were not under the HRT, which of the 60 women tested only one of them had positive sexual response, sexual rest had only indifferent or negative response. Based on the results, it is concluded that HRT can be considered as an alternative to improve sexual response of menopausal and postmenopausal women. The sexual response was positive in 36.4% for women aged 46-50 years who received hormone replacement therapy. Regarding the type of therapy used we can state that the best results were obtained with combination therapy, however, because different populations are worked with these findings must be considered only as a reference element inconclusive.